Students’ perception of emergency remote teaching in the Sultanate of Oman - Gengatharan Ramesh; Ramesh Saranya; Al-Harthy Ebtehag; Al-Badowi Khalid; Al-Habsi Zweena (Institute of Advanced Engineering and Science, 2023)
During the coronavirus disease 2019 (COVID-19) pandemic, educational institutions adopted emergency remote teaching (ERT) practices. In ERT, courses are taught online by teachers who have experience with face-to-face classroom instruction. Students and teaching staff were concerned about the sudden change to ERT and learning practices. Higher education institutions (HEIs) need to understand students’ perceptions of ERT in order to prepare appropriate strategies for online teaching and learning. This study is intended: i) to analyze the students’ perception of ERT and ii) to explore the factors that determine the effectiveness of ERT during pandemic periods. The researchers used an online survey method to collect the primary data by employing a structured questionnaire. They employed the purposive sampling technique for this study. The results of the study highlight the fact that students prefer to take advantage of the available learning opportunities during the pandemic period. This is because they can earn their academic qualifications on time. It is also evident that the sudden transition to online teaching did compromise the efficacy of academic delivery to a certain extent. The study also found that motivation and assessment were crucial factors in determining the effectiveness of ERT during the pandemic period.